تأثير التمارين عالية الشدة متعددة النماذج على مريضات سرطان الثدي الخاضعات للمعالجة الكيماوية - غزال, سوسن (Latakia University Journal -Medical Sciences Series, 2013)
يهدف البحث لتقييم تأثير تداخل متمم للرعاية التقليدية لمجموعة من التمارين الجسمانية المتعددة النماذج على التعب، الكفاءة الجسمانية، السلامة العامة، النشاط الجسماني، ونوعية الحياة لمريضات السرطان اللواتي يخضعن للعلاج الكيماوي كعلاج مكمل. أجري البحث في مشفى تشرين الجامعي في اللاذقية على عينة قوامها 164 امرأة مصابة بسرطان الثدي. تكونت التمارين من تدريب شديد مقاوم قلبي وعائي، استرخاء وتدريب الإدراك الجسدي، التدليك. طبق التمرين لمدة 9 ساعات أسبوعياً لمدة ستة أسابيع بالإضافة للرعاية التقليدية، وقورن مع مجموعة أخرى قدمت لها الرعاية التقليدية فقط. أظهرت المجموعة التجريبية تحسنا في المقاييس البدئية بعد ستة أسابيع من تطبيق التمارين، التعب-6،8 (-12،3 إلى -0،9) (P= 0،002). ولوحظت تأثيرات ذات دلالة إحصائية على الوظيفة الجسمانية 2،5 (-0،4 إلى 5،2)، الوظيفة الجسمانية 4،5 (-1،8إلى 11،1)، الوظيفة العاطفية -0،3 (-4،0 إلى 3،3)، والوظيفة العقلية 1،9 (-2،5 إلى 6،1)، بينما لم يلاحظ تأثير كبير على الوضع نوعية الحياة. يقلل تطبيق التمارين عالية الشدة متعددة النماذج بما في ذلك المكونات عالية ومنخفضة الشدة التعب ويحسن الحيوية ، والقوة العضلية، والنشاط الجسماني والوظيفي والعاطفي، ولكن لا يؤثر على نوعية الحياة في المريضات المصابات بسرطان الثدي اللواتي كن يتلقين العلاج الكيماوي. The aime of this study is to assess the effect of a multimodal group exercise intervention, as an adjunct to conventional care, on fatigue, physical capacity, general wellbeing, physical activity, and quality of life in patients with breast cancer who were undergoing adjuvant chemotherapy. The study was conducted in Tishreen university hospital in Lattakia,.the participants were 164 women with breast cancer. Supervised exercise comprising high intensity cardiovascular and resistance training, relaxation and body awareness training, massage, nine hours weekly for six weeks in addition to conventional care, compared with conventional care. The intervention group showed an estimated improvement at six weeks for the primary outcome, fatigue, of −6.8 (−12.3 to −0.9), P=0.02. Significant effects were seen on vitality for physical functioning 2,5 (-0,4 to 5,2), role physical 4,5 (-1,8 to 11,1), role emotional -0,3 (-4,0 to 3,3), and mental health 1,9 (-2,5 to 6,1) scores. No significant effect was seen on global health status/quality of life. A supervised multimodal exercise intervention including high and low intensity components was feasible and could safely be used in patients with breast cancer who were receiving adjuvant chemotherapy or treatment for advanced disease. The intervention reduced fatigue and improved vitality, muscular strength, and physical and functional activity, and emotional wellbeing, but not quality of life.